Humanities PhD Graduates: Desperately Seeking Careers? - McAlpine, Lynn; Austin, Nichole (Canadian Journal of Higher Education, 2018)
National and international statistics show that across disciplines there are many more PhD graduates than academic positions. In fact, more than half of graduates find their careers outside the academy—though the kinds of positions they accept, their work satisfaction, and the relevance of their PhDs is much less clear. As regards scholarly studies on post-PhD careers, most have examined social scientists and scientists with little attention to humanities doctoral graduates. This study addresses this gap by exploring the career experiences of Canadian PhD humanities graduates through descriptive statistics and narrative analysis. Specifically, it highlights the PhD experiences and post-graduation career trajectories of 212 Canadian humanists from 24 universities who graduated between 2004 and 2014. The study offers insight into humanities career challenges, including during the PhD, the range of non-academic careers that humanists find, as well as their work satisfaction and the perceived relevance of the PhD.